E-Modul Berbasis Android Menggunakan Flip Pdf Coporate Materi MS Word - Farhan Ammar Wahyudin; Celine Aloyshima Haris (Universitas Pendidikan Muhammadiyah Sorong, 2026)
This research aims to develop an Android-based digital module using Flip Pdf Corporate Ms Word material at SMP Negeri 5 Samarinda. This research uses a research and development (R&D) method with a 4D development model (Define, Design, Develop, Disseminate). The research subjects were 74 students. The research instruments included a validation questionnaire from media experts, material experts, student responses, and teacher responses. The results showed that the e-module obtained a feasibility score of 90% from media experts, 90% from material experts, 77.62% from students with a feasible category, and 90% from teachers with a very feasible category.